THE INFLUENCE OF AGENT COMMUNICATION, COMPETENCE, AND CREDIBILITY ON CUSTOMER LOYALTY AT PT PRUDENTIAL LIFE ASSURANCE MEDAN - Devita; Fauzi Aris Lubis; Isnaini Harahap (SOSIOEDUKASI, 2025)
As public awareness of the importance of insurance increases, the need for professional and competent insurance agents is increasing. Insurance agents are the spearhead of companies in reaching out to the public, conveying accurate information, and building trust. This study aims to analyze the influence of agent communication, competence, and credibility on customer loyalty at PT Prudential Life Assurance Medan. This study uses a quantitative approach with a survey method through the distribution of questionnaires to 100 customer respondents. The data were analyzed using multiple linear regression, partial test (t), simultaneous test (F), and classical assumption test. The results of the study show that partially, communication, competence, and credibility of agents have a positive and significant effect on customer loyalty. Simultaneously, these three variables contribute 90% to increased customer loyalty, as shown by the adjusted R² value. These findings reinforce the theory that quality service involving effective communication, professional competence, and high agent credibility is decisive in building long-term relationships with customers. Thus, insurance companies need to integrate these three aspects in their customer service management strategy. The implications of communication and competence in management are profound, where effective communication ensures organizational goals are understood and improves employee performance, while high competence drives superior performance through knowledge and skills. The two are interrelated; Good communication allows for the development of competencies, creates a positive work environment, and ultimately improves the overall performance of the organization.